Tumor-derived SEMA7A regulates fatty acid oxidation in the tumor-associated macrophages to promote the progression of non-small cell lung cancer - Wang, Jia; Shao, Yang; Zhang, Jiameng; Han, Fangfang; Wang, Si; Liu, Beixing (Frontiers in Immunology, 2025)
Non-small cell lung cancer (NSCLC) is an aggressive cancer with a poor prognosis. Despite the success of therapies for NSCLC, more investigations of new biomarkers for patient selection are urgently needed. Semaphorin 7A (SEMA7A), a soluble tumor-derived molecule, can modulate the proliferation, invasion and angiogenesis of multiple types of cancers. However, whether SEMA7A contributes to the progression of NSCLC is still unknown. In this study, by using bioinformatics analysis and an experimental murine tumor model, we found that the expression levels of SEMA7A were elevated in the human NSCLC and positively correlated with the poor prognosis. Knockdown of SEMA7A in cancer cells may suppress NSCLC progression, in parallel with a diminished M2 polarization in the tumor microenvironment (TME). In fact, SEMA7A may increase the polarization of tumor-associated macrophages (TAMs) toward the M2 phenotype in an ITGB1-dependent manner. Fatty acid oxidation in macrophages seems to be essential for the ability of SEMA7A to promote M2 polarization. Blockade of fatty acid oxidation may reverse the immunosuppressive phenotype of TAMs and the outcomes of NSCLC. Our findings provide experimental evidence that SEMA7A may act as a regulatory factor for macrophage lipid metabolism, which influences the polarization status of TAMs.